THE US STRATEGY OF ARMED DRONE USAGE IN FIGHTING THE TALIBAN ELEMENTS IN PAKISTAN (2004-2016) - Nisrina Nadhifa; Anak Agung Banyu Perwita (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
Prior to the Trump’s presidency the US have performed as many as 400 armed drone strikes in Pakistan, killing approximately 3.000 terrorist targets including key leaders that hold important value to the organizations. More than a decade these attacks were performed, yet we have not seen the end of the terrorist and insurgent’s presence in Pakistan. This leads into a thought whether the attacks were effective or not. Therefore, this study aims to analyze, predominantly  evaluating the use of the targeted killing strategy in this US counterterrorism effort. The study uses qualitative research method by using Robert A. Pape’s perspective in strategic effectiveness and David Galula’s counterinsurgency perspective. Those perspectives pointed out the cause of this situation is due to the inability of the attacked target set to trigger the destruction of the movement, the inability of the US to secure the ends, ways, and means of the operation which involve the dissociation between the population and the insurgents, their ability to forge proper cooperation with its local ally, and the un-favoring view of the local population toward its targeted killings practice has resulted in the infectivity of the strategy and a prolonged fight between the US and its opponent. In sum, it can be inferred that despite capable of eliminating numerous high-value targets the targeted killing strategy is deemed ineffective due to its inability to procure full destruction of its opponent and due to the inability of the US to secure the ends, ways, and means of the operation which would have increase the success of the strategy.